Catholic Charitable Social Work in the Former Czechoslovakia: With a Focus on the Czech Lands - Doležel, Jakub (European Journal of Mental Health, 2016)
Roman Catholic Charity, an organised and community-centred form of volunteer activity in social and healthcare services exceeding the framework of individual and private benevolence, had seen years of abundant and – in many aspects – still unrivalled development between the founding of the independent state of Czechoslovakia (1918) and the onset of the totalitarian Communist regime (1948). As the Communist Party took control of the country, the entire system of charity was dissolved, in contrast to the neighbouring countries of the Soviet Bloc (East Germany, Poland and Hungary) where some forms were allowed to function. The objective of the present study is to map out those dramatic changes and highlight individual key events and dates. The opening sections outline the well-developed system of charity that existed before the Communist seizure of power. The final sections present the developing trends of charitable work after the fall of Communism in 1989.